CHARACTERIZATION OF TEMPERATURE RESPONSE OF ASYMMETRIC TAPERED-PLASTIC OPTICAL FIBER-MACH ZEHNDER INTERFEROMETER - Yulianti, Ian (Universitas Negeri Surabaya, 2020)
Performance characterization of simple and low cost Mach Zehnder interferometer (MZI) using step index plastic optical fiber (SI-POF) to temperature variation is presented. The sensor consists of two tapers at several distance forming interferometer. The first taper was designed to be steep to allow excitation of cladding modes, while the second taper was gradual to supress power loss. Characterizations were done in terms of sensitivity, hysteresis and repeatability by analysing the output spectrums recorded by spectrometer at various environment temperature which are 35oC to 85oC with increment of 10oC. The results showed that the sensor has sensitivity of 0.0431 nm/oC and correlation coefficient of 0.9965. Hysteresis of 6.9×10-3was observed. In terms of repeatability, the sensor shows maximum deviation of ±3oC which was mainly resulted from fluctuation of oven temperature. Despite its high deviation, the sensor has advantages of simple fabrication process, low cost, robust and low power loss which make it as a good candidate for temperature sensor.